The Role of Trip Quality in Making the Decision to Visit Borobudur Temple - Tri Palupi Robustin; Fauziyah Fauziyah; Maulana Muhammad Riza; Mohammad Noor Khoirullah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The purpose of this research is to find out the effect hospitality, attractions, transpor, amenity on the decision to visit Borobudur Temple and To find out the influence of hospitality, attractions, transport, and amenity simultaneously on the decision to visit Borobudur Temple. This type of research is quantitative research with the population of tourists who have visited Borobudur Temple. Sampling techniques using non probability sampling, namely purposive sampling, with a sample count of 50 respondents. Multiple linear regression analysis is used in this study, with SPSS program version 17. Research results are the variable trip quality had a significant effect both partially and simultaneously on the decision to visit Borobudur Temple.